Short-Course versus Long-Course Preoperative Radiotherapy in Rectal Cancer: an Evidence Based Case report - Ayu Santika Santaningrum; Fenny Tjuatja; Giovano Andika Pradana; Hari Murti Wijaya; Jellyca Anton; Regina Wulandari; Sinta Prastiana Dewi; - Sudibio; Wahyu Diyana (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2017)
Background Surgery is the mainstay therapy for colorectal carcinoma with curative intent, while radiotherapy and chemotherapy act as adjuvant or neoadjuvant therapy. The desicion for surgery depends on tumor resectability. Neoadjuvant radiotherapy, both short-course radiotherapy (SRT) or long-course radiotherapy (LRT) with or without concurent chemtherapy, is aimed to increase tumor resectability. This article compares advantages of SRT and LRT. Method We designed a search filter using relevant synonyms for the domain: “rectal carcinoma”, “resectable”, “preoperative radiotherapy”, and “short-course”. Publications are retrieved from PubMed, Cochrane Library, and EBSCO using MESH terms and search terms in title and abstract fields. Articles’ titles and abstracts from search result are screened for relevance. Eligible articles are selected based on inclusion and exclusion criterias. Selected articles are critically appraised for methods validity. Result Six articles are included in our study, consists of four randomized clinical trials and four metaanalyses. Conclusion SRT is as effective as LRT with or without chemotherapy in terms of overall survival, disease free survival, local recurrence rate, disease metastasis rate, free resection rate, and grade 3-4 toxicity. LRT with or without chemotherapy showed superiority in increasing pathological complete response rate and sphincter preservation rate. SRT is a better choice in centers with a long waiting list.